Reservoir sedimentation management: A sustainabledevelopment challenge - Annandale, George W. (IAHR, 2020)
Suitable dam and reservoir sites are scarce resources that should be sustainably developed and managed to satisfy the needs of current and future generations. Historic and current dam development approaches do not address the issue of sustainable development (i.e. that reservoir water storage is needed for both current and future generations)